Clusters of obesogenic behaviors and metabolic risk according to somatic maturity status among adolescents - Magalhães, Kleberton C. S.; Matias, Thiago S.; Araujo, Raphael H.; Werneck, André O.; Ferrari, Gerson; Luz, Leonardo G. O.; Fernandes, Rômulo A. [UNESP]; Barbosa, Décio S.; Ronque, Enio R. V.; Cyrino, Edilson S.; Silva, Danilo R. (Wiley, 2022)
Objective: This study aimed to identify the clusters of obesogenic behaviors, and verify the association with metabolic risk according to the categories of somatic maturity status of adolescents. Methods: This is a cross-sectional study conducted with 1159 (55.1% girls) Brazilian adolescents aged between 10 and 16 years (mean age: 12.9 years). Measurements of waist circumference, blood pressure, blood glucose, HDL-C, and triglycerides were combined to calculate a metabolic risk score. Somatic maturity was assessed by estimating the peak of height velocity. The obesogenic behaviors analyzed were physical activity (Baecke questionnaire), sedentary behavior (screen-based behaviors) and dietary habits (consumption of healthy and unhealthy food). The Two Step clustering algorithm using the log-likelihood measure was employed to cluster formation and regression models were adopted to the main analysis. Results: We observed a complex co-existence of obesogenic behaviors. Differences regarding the metabolic risk between clusters was only observed among the early-maturing adolescents, where the cluster with higher number of healthy behaviors but lower physical activity presented higher metabolic risk score. Conclusions: We conclude that physical activity has an important role on the association of clusters of obesogenic behaviors and metabolic risk in early-maturing adolescents.